2009
DOI: 10.1177/1063426609339186
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Year Outcome Study of the Check, Connect, and Expect Intervention for Students At Risk for Severe Behavior Problems

Abstract: Two hundred seven students in Grades 1 through 5 who were at risk for severe behavior problems participated in a 2-year study of the effects of the Check, Connect, and Expect (CCE) program. The CCE program combined the essential intervention procedures of the Check & Connect Program and the Behavior Education Program . A stratified random sample of students based on school assignment was used to compare the outcomes of 121 CCE program students with 86 comparison students. Sixty percent of the CCE students (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 20 publications
(27 reference statements)
0
88
0
Order By: Relevance
“…In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013). Statistically significant effects were reported for students' classroom behavior (e.g., Fabiano et al, 2010;Simonsen et al, 2011); daily report cards (e.g., Cheney et al, 2008;Cheney et al, 2009); scores on the Social Skills Rating System (Gresham & Elliott, 1990;e.g., Cheney et al, 2008;Cheney et al, 2009), Teacher Rating Form (Achenbach, 2001; e.g., Cheney et al, 2009), and Behavior Assessment Scale for Children 2 (Reynolds & Kamphaus, 2004;e.g., McIntosh et al, 2009); academic productivity and success (e.g., Fabiano et al, 2010); and office discipline referrals (e.g., Hawken, O'Neill, & MacLeod, 2011;McIntosh et al, 2009).…”
Section: Cico Variationsmentioning
confidence: 99%
“…In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013). Statistically significant effects were reported for students' classroom behavior (e.g., Fabiano et al, 2010;Simonsen et al, 2011); daily report cards (e.g., Cheney et al, 2008;Cheney et al, 2009); scores on the Social Skills Rating System (Gresham & Elliott, 1990;e.g., Cheney et al, 2008;Cheney et al, 2009), Teacher Rating Form (Achenbach, 2001; e.g., Cheney et al, 2009), and Behavior Assessment Scale for Children 2 (Reynolds & Kamphaus, 2004;e.g., McIntosh et al, 2009); academic productivity and success (e.g., Fabiano et al, 2010); and office discipline referrals (e.g., Hawken, O'Neill, & MacLeod, 2011;McIntosh et al, 2009).…”
Section: Cico Variationsmentioning
confidence: 99%
“…This work may include, but not be limited to, developing new interventions. As noted previously, interventions such as Check and Connect (A. R. Anderson et al, 2004;Cheney et al, 2009; and First Step to Success (Beard & Sugai, 2004;Loman, Rodriguez, & Horner, 2010;Rodriguez, Loman, & Horner, 2009) have documented empirical support but have not yet been fully developed to fit within a multitiered framework. Thus, work is needed to define decision rules and to delineate steps needed to build and maintain capacity to implement within a school, without support from a research team.…”
Section: Future Directionsmentioning
confidence: 95%
“…Research has shown CICO to be effective in reducing problem behavior with elementary and middle school students (Bruhn, Lane, & Hirsch, 2014;Cheney et al, 2009;Fairbanks, Sugai, Guardino, & Lathrop, 2007;Filter et al, 2007;Hawken, 2006;Hawken, Bundock, Kladis, O'Keeffe, & Barrett, 2014;Hawken & Horner, 2003;Hawken, MacLeod, & Rawlings, 2007;March & Horner, 2002;McCurdy, Kunsch, & Reibstein, 2007;Miller, Dufrene, Sterling, Olmi, & Bachmayer, 2015;Todd, Kaufman, Meyer, & Horner, 2007). In a recent review of 28 studies evaluating CICO, the intervention was found to decrease observed problem behavior, improve academic engagement or work completion, improve the percentage of DPR points, and reduce Office Discipline Referrals (ODRs; Hawken et al, 2014).…”
Section: Introductionmentioning
confidence: 99%